Description of the External Genitalia and Uterus of a 24-month-old Freemartin Hanwoo - Ui-Hyung Kim; Sung-Sik Kang; Ki-Yong Chung; Boh-Suk Yang; Sang-Rae Cho (The Korean Society of Animal Reproduction and Biotechnology, 2018)
We observed the external genitalia and uterus of a 24-month-old freemartin Hanwoo. The vulva was smaller than observed in a normal female Hanwoo, while the clitoris was larger in the freemartin. The angle between the external genitalia and the perineum also varied. Upon internal genital examination, the uterus of the freemartin was a thin tube approximately 18 cm in size and had not differentiated into a normal uterus and uterine horns.